2015
DOI: 10.1038/srep07688
|View full text |Cite
|
Sign up to set email alerts
|

The tyrosine kinase Itk suppresses CD8+ memory T cell development in response to bacterial infection

Abstract: Vaccine efficacy depends on strong long-term development of immune memory and the formation of memory CD8+ T cells is critical for recall responses to infection. Upon antigen recognition by naïve T cells, the strength of the TcR signal influences the subsequent effector and memory cells differentiation. Here, we have examined the role of Itk, a tyrosine kinase critical for TcR signaling, in CD8+ effector and memory T cell differentiation during Listeria monocytogenes infection. We found that the reduced TcR si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 36 publications
(50 reference statements)
5
11
0
Order By: Relevance
“…ITK has been shown to regulate the strength of the TCR signal during T cell activation (28)(29)(30)(31). We have previously shown that reducing TCR signal strength via deletion of ITK leads to an increase in the proportion of Ag-specific CD8 + MPECs (32). This data support the theory that TCR signal strength inversely regulates the development of memory T cells.…”
supporting
confidence: 78%
“…ITK has been shown to regulate the strength of the TCR signal during T cell activation (28)(29)(30)(31). We have previously shown that reducing TCR signal strength via deletion of ITK leads to an increase in the proportion of Ag-specific CD8 + MPECs (32). This data support the theory that TCR signal strength inversely regulates the development of memory T cells.…”
supporting
confidence: 78%
“…Inducible T cell kinase (ITK) plays an important role in the maintenance of Th2 CD4+ cells and memory CD8+ T cells and is known to be inhibited by ibrutinib (5). However, Itk −/− CD8+ memory T cells (in comparison to naïve CD8+ T cells) demonstrate normal recall responses to bacterial infection in terms of frequency and functionality and this is compatible with our findings (19). The impact of ibrutinib on the induction of primary immune responses mediated by naïve T cells deserves further investigation.…”
Section: Discussionsupporting
confidence: 91%
“…The second one (memory potential, survival) would be similar to the MPEC population. This is consistent with the litterature, since Tbet is known to favour the development of SLEC, to the detriment of MPEC [7,8,9].…”
Section: Cellular Dynamics Arise From Cellular Heterogeneitysupporting
confidence: 86%
“…Transcription factors Tbet and Eomesodermin (Eomes) appear to play critical roles in the acquisition of effector and memory phenotypes. It has been shown that the expression of Tbet induces the development of SLEC and represses the development of MPEC profiles [7,8,9]. Eomes is not involved in the SLEC versus MPEC fate choice [10,11].…”
Section: Introductionmentioning
confidence: 99%